Seed bank dynamics of an invasive alien species, Helianthus annuus L - Presotto, Alejandro Daniel (2020)
AimsThe ability to form persistent seed banks is one of the best predictors of species´ potential to establish in new ranges. Wild sunflower is native to North America where the formation of persistent seed banks is promoted by disturbance and it plays a key role on the establishment and persistence of native populations. However, the role of the seed banks on the establishment and persistence of invasive populations has not been studied. Here, we evaluated the role of seed bank and disturbance on the establishment and fitness, and seed persistence in the soil in several sunflower biotypes collected in ruderal (wild H. annuus) and agrestal (natural crop-wild hybrid) habitats of Argentina as well as volunteer populations (progeny of commercial cultivars).MethodsIn a seed-bank experiment, we evaluated emergence, survival to reproduction, survival of emerged seedlings, inflorescences per plant and per plot under disturbed and undisturbed conditions over two years; in a seed-burial experiment, we evaluated seed persistence in the soil over four springs (6, 18, 30 and 42 months).Important FindingsOverall, seedling emergence was early in the growing season (during winter), and it was promoted by disturbance, especially in the first year. Despite this, the number of inflorescences per plot was similar under both conditions, especially in ruderals. In the second year, emergence from the seed bank was much lower, but the survival rate was higher. In the seed-burial experiment, genetic differences were observed but seeds of ruderals and agrestals persisted up to 42 months while seeds of the volunteer did not persist longer than 6 months. The agrestal biotype showed an intermediate behavior between ruderals and volunteers in both experiments. Our findings showed that wild and crop-wild sunflower can form persistent seed banks outside its native range and that disturbance may facilitate its establishment in new areas.